The beta(4)-Subunit of the Large-Conductance Potassium Ion Channel K(Ca)1.1 Regulates Outflow Facility in Mice - Bertrand, Jacques A.; Schicht, Martin; Stamer, W. Daniel; Baker, David; Sherwood, Joseph M.; Luetjen-Drecoll, Elke; Selwood, David L.; Overby, Darryl R. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. The large-conductance calcium-activated potassium channel K(Ca)1.1 (BKCa, maxi-K) influences aqueous humor outflow facility, but the contribution of auxiliary beta-subunits to K(Ca)1.1 activity in the outflow pathway is unknown.
CRIS-Team WoS Importer:2020-04-21